MANTLE DYNAMICS: THE STRONG CONTROL OF THE SPINEL-PEROVSKITE TRANSITION AT A DEPTH OF 660 KM - Schubert G.; Tackley P.J. (My University, 1995)
The strong control that the endothermic phase change from spinel to perovskite and magnesiowustite at a depth of 660 km has on mantle convection is discussed. The phase transition determines the morphology and length scales of upflow and downflow structures and, through retardation of sinking slabs, can cause an avalanche phenomenon involving rapid flushing of cold upper mantle material down to the base of the lower mantle. The phase change significantly heats plumes that rise from the lower mantle and penetrate into the upper mantle. The exothermic phase change from olivine to spinel at a depth of 400 km in the mantle mitigates the effects of the dynamically and thermally dominant endothermic phase transition.